2015
DOI: 10.2169/internalmedicine.54.3784
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after Radiotherapy for Gastric Mucosa-associated Lymphoid Tissue (MALT) Lymphoma with Trisomy 18

Abstract: A 36-year-old Japanese woman presented with extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) in the stomach. The gastric lesions only partially improved after eradication therapy for Helicobacter pylori. A fluorescence in situ hybridization analysis revealed no fusion genes of API2-MALT1, although trisomy of chromosome 18 was identified. Radiation therapy was initiated to treat the gastric lymphoma lesions, resulting in complete remission. However, MALT lymphoma recurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Aneuploidy - most commonly trisomy 18, trisomy 3, or both - is frequently observed in t(11;18)(q21;q21)/ API2-MALT1 -negative MALT lymphoma ( 17 - 20 ). The presence of extra copies of MALT1 is significantly associated with the progression or relapse of lymphoma ( 21 , 22 ), and it is an independent prognostic factor for a worse event-free survival, as determined by a Cox multivariate analysis ( 21 ). Previous studies have suggested that numerical gains, such as trisomy 3 or 18, are associated with the high-grade transformation of MALT lymphoma ( 18 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aneuploidy - most commonly trisomy 18, trisomy 3, or both - is frequently observed in t(11;18)(q21;q21)/ API2-MALT1 -negative MALT lymphoma ( 17 - 20 ). The presence of extra copies of MALT1 is significantly associated with the progression or relapse of lymphoma ( 21 , 22 ), and it is an independent prognostic factor for a worse event-free survival, as determined by a Cox multivariate analysis ( 21 ). Previous studies have suggested that numerical gains, such as trisomy 3 or 18, are associated with the high-grade transformation of MALT lymphoma ( 18 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the pathogeneses of the two diseases, the similarities in the endoscopic images observed in the present case and the case of plasmacytoma reported by Harada et al [ 6 ] may reflect common pathological features shared between the two cases, for example, proliferation of plasma cells. However, further studies are required to determine the macroscopic morphologies of gastric MALT lymphoma with increased plasma cell differentiation, as we had previously encountered another case of this disease, which showed a lack of gastric pits and the presence of abnormal vessels [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of gastric MALT lymphoma with plasma cell differentiation was made based on these pathological features. Fluorescence in situ hybridization (FISH) analysis for t(11;18)(q21;q21) translocation revealed no fusion genes of BIRC3-MALT1 , although extra copies of MALT1 were identified in 32.0% of the monocytoid cells ( Figure 4 ), indicating trisomy of chromosome 18 [ 2 , 7 ]. Chromosome banding of the bone marrow aspirate showed a normal karyotype of 46, XX, indicating no congenital chromosomal abnormalities.…”
Section: Case Reportmentioning
confidence: 99%
“…Statistical analysis revealed that the time to recurrence was significantly shorter in patients with trisomy 18 than in those without trisomy 18 ( P = 0.05). We also reported a patient with gastric MALT lymphoma with trisomy 18 in whom only partial improvement was documented after eradication therapy for H. pylori , and lymphoma recurred in the stomach 16 months after radiotherapy[ 5 ]. On the other hand, Taji et al[ 17 ] retrospectively reviewed 13 patients with localized MALT lymphoma in the stomach, and reported that all patients with unresponsive or progressive disease had t(11;18) translocation or trisomy 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported a case of gastric MALT lymphoma with trisomy 18[ 5 ]. In that case, although there were no fusion genes of API2-MALT1 , trisomy 18 was identified as extra copies of MALT1 , using a fluorescence in situ hybridization (FISH) analysis for t(11;18)(q21;q21)/ API2-MALT1 translocation, since MALT1 is located on chromosome 18q21.…”
Section: Introductionmentioning
confidence: 99%